EFFECT OF Nb ELEMENT CONTENT IN U-Zr ALLOY ON HARDNESS, MICROSTRUCTURE AND PHASE FORMATION - Masrukan, Masrukan; Al Hasa, M. Husna; Setiawan, Jan; Pribadi, Slamet (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
EFFECT OF Nb ELEMENT CONTENT IN U-Zr-Nb ALLOY ON HARDNESS, MICROSTRUCTURE AND PHASE FORMATION. Experiments to determine the effect of Nb element in the U-Zr alloys on hardness, microstructure and phase formation has been done. The addition of Nb element would effect the hardness, microstructure and phase which formed. The U-Zr-Nb alloy was made with the variation of Nb 2%, 5% and 8% by melting in an electric arc melting furnace that equipped with water cooling and the argon atmosphere. The U-Zr-Nb alloy to be cut divided to some testing, such as hardness test, microstructure, and phase analysis. Hardness testing was done by Vickers hardness testing equipment, microstructure by an optical microscope, and diffraction pattern by XRD and phase analysis was done by GSAS. Hardness testing results showed that the addition of 2% to 5% Nb element in U-Zr alloys will increased in hardness, but the addition of Nb element over 5% the hardness was decreased. Observations the microstructure showed that the addition of 2% to 5%Nb element, grains were formed from fine into coarse. Phase analysis for diffraction pattern showed that the phase changed from αU and γU (Zr,Nb)at 2% Nb to be αU, γU (Zr,Nb) and δ1 (UZr2) phase at 5% and 8% Nb. Phase changes was followed by changes in its compositions. The composition of αU at 2% Nb was 40% increased to 81% at 5% Nb and decreased to 3.9% at 8% Nb. The composition of γU decreased from 59,86% to 14,91% with increased Nb from 2% to 5% and further increased to 52,74% at 8% Nb.